2014
DOI: 10.1098/rspa.2014.0370
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of mergers and acquisitions: ancestry as the seminal determinant

Abstract: Understanding the fundamental mechanisms behind the complex landscape of corporate mergers and acquisitions is of crucial importance to economies across the world. Adapting ideas from the fields of complexity and evolutionary dynamics to analyse business ecosystems, we show here that ancestry, i.e. the cumulative sum of historical mergers across all ancestors, is the key characteristic to company mergers and acquisitions. We verify this by comparing an agent-based model to an extensive range of business data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
(17 reference statements)
2
6
0
Order By: Relevance
“…where we have used (11) and we write v = max (k v ) as the largest of the shortest path lengths from vertex v which has degree k v . Not surprisingly this is dominated by the distance to the further nodes as in the tree they are the dominant contribution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…where we have used (11) and we write v = max (k v ) as the largest of the shortest path lengths from vertex v which has degree k v . Not surprisingly this is dominated by the distance to the further nodes as in the tree they are the dominant contribution.…”
Section: Discussionmentioning
confidence: 99%
“…Fig 1. The different colours label them as different communities which are the structural characteristics in the network science context. As in the graph, 1-12 shareholders are categorised into 4 communities, 12 belongs to one community, 2,3,4,5,6 belong to another community, 8,9,10,11 are in the third community and 1,7 are in the fourth community. Table 3.…”
Section: Community Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis and modeling of our society is providing profound new insights such as cascading failures 1 and resilience 2 , 3 using the lens of the science of complex systems 4 7 . In earlier research on a national network of transactions between businesses, which can be regarded as a typical real world example of a complex network having both the basic properties of small world 8 and scale-free 9 accompanied with various scaling relations 10 18 , it was found that the balance between new entry, bankruptcy and merger plays the key role in the time evolution of this system 19 , 20 . Here, we focus on the recent comprehensive data of Mergers and Acquisitions (“M&A”) in Japan, more than 41 thousands events, and find that the network evolution is essentially unstable due to two basic inherent business dynamics; the preferential selection, whereby acquiring companies tend to be bigger than their targets, and concentrative M&A, in which the probability of merger among bigger companies is higher.…”
Section: Introductionmentioning
confidence: 99%
“…Here, without making any judgement about merits and disadvantages of distinct economic systems, we note that a centralised style communist system can be regarded as an extreme case of preferential attachment since virtually almost all market agents will almost solely trade with the largest entities (i.e., governments and large public companies). Yet, the current Western 'capitalist' system also tends to lead to a virtual monopoly by the largest companies [9,20]. Therefore, one can reasonably argue that Western-style developed economies are no longer structurally capitalist, typically underpinned by a free market configuration.…”
Section: The Economic Dimensionmentioning
confidence: 99%